Micronutrient Fortification in Early Childhood: Knowledge, Attitudes, and Practices among Mothers of Preschool Children in Kochi, Kerala, India - Thomas, Treesa Sindhu P.; Leon, Leena (Asian Journal of Biological and Life Sciences, 2026)
Background: This study aims to evaluate the Knowledge, Attitudes, and Practices (KAP) of mothers of preschool children regarding micronutrient fortification. Materials and Methods: A total of 200 mothers from Kochi, Kerala, India, participated in the survey, which was conducted using a structured questionnaire. Results: The findings revealed high levels of awareness (85%) and positive attitudes (70% considering it very important) towards micronutrient fortification. However, only 55% of mothers reported including fortified foods in their child's diet regularly. Key barriers identified included cost (40%) and availability (30%). Inferential statistical analyses, including the Chi-Square test and independent samples t-test, indicated a significant association between education level and awareness (χ²(4, n=200)=12.56, p<0.05) and a significant difference in attitudes between employed mothers and homemakers (t(198) = 2.34, p<0.05). Conclusion: The study underscores the need for public health initiatives to address barriers and promote the inclusion of fortified foods in children's diets. Interventions focusing on making fortified foods more affordable and accessible, along with continuous education, are recommended to bridge the gap between knowledge and practice. Future research should explore long-term impacts and effective strategies to improve micronutrient fortification practices.
Keywords: Fortified Foods; Hidden Hunger; Kochi; Kerala; Maternal KAP; Micronutrient; Fortification; Preschool Children